PERAN PLATELET RICH PLASMA PADA REGENERASI SARAF (Jurnal Sinaps, 2023)
Nerve cell regeneration is the regrowth or recovery of nerve tissue, cells, or products from cells after injury. Peripheral nerves that are injured will undergo a series of complex and coordinated processes to remove damaged tissue and start the repair process which will eventually undergo a regeneration process. Platelet rich plasma (PRP) is an autologous blood sample that has a platelet concentration above the normal level contained in blood plasma. Platelet rich plasma is rich in growth factors such as platelet derived growth factor (PDGF), transforming growth factor–β (TGF-β), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), Insulin-like Growth Factor 1,2 (IGF-1, IGF-2) and Fibroblast Growth Factor (FGF). Platelet rich plasma can increase Schwann cell proliferation, migration of Schwann cells and synthesis of extracellular matrix such as collagen which has benefits in nerve regeneration. Platelet rich plasma has a positive effect on nerve regeneration. The neuroregenerative and neuroprotective potential of PRP depends on the amount of growth factor released upon activated platelets. Platelet rich plasma with high growth factor can act as a catalyst to speed up the healing process and nerve regeneration.